Established church, sectarian people: itinerancy and the transformation of English dissent, 1780-1830 - Lovegrove, Deryck W. (Cambridge University Press, 1988)
This book examines a neglected aspect of English social history - the operation of itinerant preachers during the period of political and social ferment at the turn of the nineteenth century. It investigates the nature of their popular brand of Christianity and considers their impact upon existing churches: both the threat apparently posed to the established Church of England and the consequences of their activity for the smaller Protestant bodies from which they arose. The particular strength of the book lies in the extensive use it makes of previously untapped local archives drawn from many English counties - records which include numerous parochial, legal, associational and congregational sources. This is a study of religion in transition which is set against the wider canvas of social change attendant upon the early Industrial Revolution and the political shock waves emanating from France.